POTENTIAL EFFECTS OF CRYPTOCURRENCIES ON MONETARY POLICY - Tomić, Nenad; Todorović, Violeta; Čakajac, Božidar (The European Journal of Applied Economics, 2020)
All current cryptocurrencies are controlled by private entities, so that the issue of impact to monetary system becomes very important. Autonomous decisions of private entities about money supply could diminish the ability of central banks to implement monetary policy effectively. The subject of this paper is the influence of alternative cryptocurrencies forms on monetary system. The aim of the paper is to determine the ability of central banks to conduct monetary policy successfully in conditions of widespread use of cryptocurrencies in payment transactions. The situation in the cryptocurrencies’ market is compared with the phases of the Internet development and the current situation on other markets of electronic payment systems. It is concluded that, cryptocurrencies do not have the capacity to endanger the traditional monetary system at the current level. Bearing in mind early maturity of this market, certain predictions of possible future trends have been made. In the case of private cryptocurrencies usage growth, it could happen that the central banks partially or completely lose the influence over monetary policy. The proposed solution is the development of national cryptocurrencies that would ensure the retention of seigniorage to central banks and prevention of further use of private cryptocurrencies in criminal activities.